Sistem Pendukung Keputusan Pemilihan Pakan Ternak dari Sisa Penggilingan Padi Menggunakan Metode Fuzzy Tsukamoto - Erta Susanti; Raheliya Br Ginting; Nirwan Sinuhaji; Meiliyani Br Ginting (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
on the process, processed rice not only produces rice, but also produces several forms of waste such as husk ash, bran, and rice bran. Rice husk ash is a hard layer that includes kariopsis which consists of two halves called lemma and palea which are interconnected. From the remnants of the rice mill, it can also be used optimally as animal feed. Feed is a mixture of various kinds of organic materials given to livestock to meet the needs of nutrients needed for growth, development and reproduction. The problem faced by this team is how to determine animal feed from the rest of the rice mill. Based on these problems, the authors designed an application system that was built using Matlab software which combines fuzzy logic programs and Matlab GUI as the application display.